Accelerator techniques and nuclear data needs for ion beam analysis of wall materials in controlled fusion devices - Marek Rubel; Daniel Primetzhofer; Per Petersson; Sotirios Charisopoulos; Anna Widdowson (EPJ Techniques and Instrumentation, 2023)
Abstract A brief overview of ion beam analysis methods and procedures in studies of materials exposed to fusion plasmas in controlled fusion devices with magnetic confinement is presented. The role of accelerator techniques in the examination and testing of materials for fusion applications is emphasised. Quantitative results are based on robust nuclear data sets, i.e. stopping powers and reaction cross-sections. Therefore, the work has three major strands: (i) assessment of fuel inventory and modification of wall materials by erosion and deposition processes; (ii) equipment development to perform cutting-edge research; (iii) determination of nuclear data for selected ion-target combinations. Advantages and limitations of methods are addressed. A note is also given on research facilities with capabilities of handling radioactive and beryllium-contaminated materials.